2019
DOI: 10.1111/ans.15228
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in clinically node‐negative Merkel cell carcinoma: the Westmead Hospital experience

Abstract: Background: Merkel cell carcinoma (MCC) is a rare, aggressive cutaneous malignancy with a propensity to metastasize to regional lymph nodes. Sentinel lymph node biopsy (SLNB) in patients with clinically node-negative MCC has been utilized to identify patients with subclinical nodal metastases. This study aims to review the accuracy of SLNB in MCC and to evaluate the impact of SLNB on management. Methods: Patients with clinically node-negative MCC who underwent SLNB were identified from a prospective database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…12 In the absence of prospective data, reports have suggested that RT to the draining lymph node basin can be omitted for SLNB-negative patients, citing a low risk of regional recurrence. 3,[5][6][7] However, in these retrospective studies, regional relapse rates for these patients were 11% to 17% with overall relapse as high as 20% to 30%, and radiation fields were not uniform. 9 In this context, the over-riding goal of our study was to evaluate the low risk of regional recurrence when only the primary site was irradiated after a negative SLNB.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…12 In the absence of prospective data, reports have suggested that RT to the draining lymph node basin can be omitted for SLNB-negative patients, citing a low risk of regional recurrence. 3,[5][6][7] However, in these retrospective studies, regional relapse rates for these patients were 11% to 17% with overall relapse as high as 20% to 30%, and radiation fields were not uniform. 9 In this context, the over-riding goal of our study was to evaluate the low risk of regional recurrence when only the primary site was irradiated after a negative SLNB.…”
Section: Discussionmentioning
confidence: 80%
“…Some studies suggest adjuvant nodal RT can be safely omitted in SLNB-negative disease, citing low rates of regional recurrence. 3,[5][6][7] However, other studies demonstrate regional recurrence rates as high as 33% even in SLNB-negative patients, raising concern about the draining lymph nodes in this population. 22 Here, we report a 20-year experience treating MCC with adjuvant RT according to a policy of excluding the draining nodal basin for SLNB-negative MCC and including the draining nodal basin for SLNB-positive MCC.…”
Section: Introductionmentioning
confidence: 97%
“…Für Patienten mit Primärtumoren mit einem Durchmesser < 2 cm liegt das Fünfjahresüberleben bei 63–75%, für Primärtumoren mit einem Durchmesser > 2 cm bei 35–60%, für Patienten mit Lymphknotenmetastasen 27–52%, und für Patienten mit Fernmetastasen zwischen 13–18% 2,15,17–20 . Daher ist es nicht überraschend, dass Tumorbefall des Schildwächterlymphknotens ein wesentlicher prognostischer Parameter ist, der mit einer deutlich schlechteren Prognose einhergeht; da umgekehrt ein tumorfreier Schildwächterlymphknoten mit einer besseren Prognose assoziiert ist, werden Patienten mit nicht durch Schildwächterlymphknotenbiopsie gesicherten Lymphknotenstatus in der aktuellen Stadieneinteilung der AJCC einer intermediären Risikogruppe zugeordnet 21,22 . Zusätzlich wird der Anzahl an befallen Lymphknoten beziehungsweise dem Lymphknoten‐Ratio (lymph node ratio; LNR: Anteil positiver an untersuchten Lymphknoten) eine prognostische Bedeutung zugeschrieben.…”
Section: Allgemeinesunclassified
“…However, SLNBs have been shown to be the most efficacious in the staging and prognostication, rather than the treatment, of MCC. Clinically node‐negative MCCs may demonstrate nodal positivity in SLNB assessment in as high as 48% of MCC cases 7,9 . On the other hand, SLNBs have been found to have a false‐negative rate of 16% 9 .…”
Section: Mcpyv‐positive Merkel Cell Carcinoma and Treatmentmentioning
confidence: 99%
“…Clinically node‐negative MCCs may demonstrate nodal positivity in SLNB assessment in as high as 48% of MCC cases 7,9 . On the other hand, SLNBs have been found to have a false‐negative rate of 16% 9 . Patients that undergo SLNBs have been shown to have an increased 5‐year survival MCC‐specific survival rate compared to observation groups (79.2% vs. 73.8%; P = 0.004), but this outcome can also be attributed to the fact that patients receiving SLNB are younger, are more likely to receive radiotherapy, and have early stage tumors, thus, the independent benefit of SLNB on survival could not be fully ascertained 10 …”
Section: Mcpyv‐positive Merkel Cell Carcinoma and Treatmentmentioning
confidence: 99%